Failure mode in upper endodontic premolars, rehabilitated with lithium disilicate crowns - Balladares Araujo, Grace Anabel (2022)
Factors such as the reduction of existing dental tissue after an endodontic treatment, the design of the carving and the restorative material condition the success of rehabilitation. Objective: To evaluate the compressive strength and failure mode against axial forces of endodontics upper premolars rehabilitated with lithium disilicate crowns. Methodology: thirty healthy upper premolars, which will be randomly classified into three groups, one control group and two experimental ones, all the teeth will be endodontically treated and rehabilitated with lithium disilicate crowns The samples will be subjected to 5000 before being subjected to axial compressive forces with the universal force machine. Results: the compressive strength values are 675.7 N for the control group (D), 1118.5 N for the glass fiber post and crown (C), and 1403.9 N for the endocrowns group (E). The values of endocrowns, to the statistical ANOVA test is of p = 0.000, which indicates that there is a statistically significant difference, to the analysis by pairs, by Tukey’s Post Hoc test, (D) and (C) p = 0.020, (D) with (E) p = 0.000. The Student’s T-test shows Endocrown is the one that most resists compression. Regarding the failure mode, when performing the Chi-square test we have a p = 0.301 between the experimental groups, that is to say that, there is no statistically significant difference of the results obtained in terms of the failure modes. Conclusion: the endocrown is the recommended procedure.